2003
DOI: 10.1046/j.1540-8175.2003.03025.x
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing Spondylitis in Association With Mitral Stenosis, Mitral Regurgitation, and Aortic Regurgitation: A Case Report and Review of the Literature

Abstract: We report on a patient with ankylosing spondylitis in association with mitral stenosis, mitral regurgitation, and aortic regurgitation. Despite extensive search of literature, we could not find association of mitral stenosis with ankylosing spondylitis. This report is the first to describe this association. Our findings are based on clinical and echocardiographic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The most commonly encountered valve disease in ankylosing spondylitis patients are the aortic and mitral insufficiency. 31,44 Valvular disease, especially aortic stenosis, may contribute to the impairment of diastolic functions. 45 In our study mild valvular abnormalities were observed in only few subjects, both in the patient and control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly encountered valve disease in ankylosing spondylitis patients are the aortic and mitral insufficiency. 31,44 Valvular disease, especially aortic stenosis, may contribute to the impairment of diastolic functions. 45 In our study mild valvular abnormalities were observed in only few subjects, both in the patient and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly encountered valve disease in ankylosing spondylitis patients are the aortic and mitral insufficiency 31, 44 . Valvular disease, especially aortic stenosis, may contribute to the impairment of diastolic functions 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitral stenosis in association with ankylosing spondylitis has been reported on a single occasion. 10 This occurred in association with mitral and aortic regurgitation and was postulated to relate to fibrous thickening of the mitral valve leaflets resulting in restricted opening. It is impossible, however, to exclude intercurrent rheumatic fever as a cause of the valvular abnormalities in this report.…”
Section: Mitral Regurgitationmentioning
confidence: 99%